Epistemology of Interpretation in the Era of Artificial Intelligence: Authority, Validity, and the Limits of AI’s Role in Quranic Interpretation - Akhmetkazy Bagasharov; Mamyrova Zhantaeva; Kuzembayeva Khalizhan; Yemelianova Kurmanbayev; Nurgazy Khaydarov (Yayasan Albahriah Jamiah Indonesia, 2026)
The development of artificial intelligence in Islamic studies has transformed the landscape of the production and circulation of Quranic exegetical knowledge, while simultaneously raising epistemological issues that have not been systematically discussed, particularly regarding the shift in interpretive authority, the criteria for the validity of exegetical expertise, and the limits of technology’s role in understanding the sacred text. Previous studies tend to position AI as a technical instrument or discuss it normatively, while its epistemological implications for the structure and legitimacy of exegesis have received little attention. This article critically analyzes the relationship between Quranic exegesis and artificial intelligence by formulating the epistemological limits of AI’s role within the framework of contemporary exegetical epistemology. This study employs a qualitative approach, utilizing an epistemological-critical analysis method grounded in Islamic epistemology and contemporary philosophy of science, as reflected in classical and modern exegetical literature. The results reveal a shift in the pattern of exegetical authority, where AI serves as an epistemic mediator that facilitates linguistic, intertextual, and comparative analysis while remaining dependent on human interpretative authority. The construction of the data corpus determines the validity of AI-based interpretation, the epistemic assumptions internalized in the algorithm, and AI’s limitations in capturing the historical, social, and discursive context of the Quran. AI also lacks the reflective capacity, hermeneutic intentionality, and intellectual accountability that are essential requirements for interpretation. In conclusion, AI must be epistemologically positioned as an analytical aid, not an authoritative source of interpretation, with theoretical implications that strengthen the epistemological framework of interpretation, making it adaptive to technology without obscuring the principles of scientific validity and the authority of human interpreters.